Miniature jet engine compressor design and optimization - Goh, Aik Tio. (2012)
With the proliferation of unmanned aerial vehicles (UAVs) in today’s modern battlefield, the key to enhancing their range is to design a high performance mini-jet engine. One of the key components of the mini-jet engine is the centrifugal compressor. In this study, a design strategy for two centrifugal compressors suitable for use in the SR-30 mini-jet engine was developed. The meanline software, Compal, was used to generate an initial design. Optimization of the meanline models was performed. After which, the models was transferred to the numerical simulation software Axcent where modifications were made to the three-dimensional geometry before conducting the full three-dimensional computational fluid dynamics (CFD) simulations. The first design was accomplished using the design of experiments (DOE) technique. The parametric studies conducted provided the necessary understanding of the influence of the design variables on the compressor stage performance. In particular, the decrease in the inlet hub radius and the backsweep angle were found to have significant positive impacts on the stage pressure ratio. On the other hand, an increase in the backsweep angle increased the compressor efficiency. For the second design of the compressor, the feasibility of an automated optimization search technique was investigated. The optimization software TurboOpt II and IOSO NM were used. Both optimizations were carried out in the meanline software to reduce the time taken in the design cycle. At the design point of 80,000 rpm and 0.3 kg/s mass flow rate, the first design achieved 11.2 % increase in the pressure ratio and 8.2 % increase in the efficiency. The second design achieved similar increase in the pressure ratio and 10.9 % increase in the efficiency. Deeper analysis of the CFD results revealed that the second compressor exhibits more desirable flow characteristics at the inducer and diffuser. Further improvements to the stage performance appear to be achievable by using IOSO to optimize the meridional and blade angle distributions of the impeller to produce a more uniform outlet flow. The detailed stress and modal analysis is suggested to be performed in future.